INFLUENCE OF EXTERNAL ORGANIZATIONAL ENVIRONMENT ON PERFORMANCE OF COMMUNITY-BASED HIV AND AIDS ORGANIZATIONS IN NAIROBI COUNTY, KENYA - Jane, Njuguna-Kinyua; Justus, Munyoki; Francis, Kibera (European Scientific Journal, ESJ, 2014)
As the external organizational environment continue to be turbulent, affecting activities for both profit and non-profit organizations, organizations are becoming more concerned with their performance so as to ensure that the available but limited resources are utilized efficiently and effectively. Over time, attention has been focused on profit-making organizations with little emphasis on performance of community-based organizations (CBOs) especially those located in Sub-Saharan Africa. Theoretically, scholars in management discipline indicate that the external environment of an organization influences its performance. Thus, an organization’s level of performance is dependent on dynamism and complexity of the external environment, heterogeneity as well as capacity and domain consensus of the existing organizations. This paper examines the impact of the external organizational environment on performance of community-based HIV and AIDS organizations in Nairobi County, Kenya. The authors empirically assess the predicted relationship using survey data from 163 Community Based HIV and AIDS Organizations, in Nairobi County, Kenya between January and March 2013. The study findings indicate that the external environment of an organization has an impact on an organization’s effectiveness, efficiency, relevance and financial viability with higher impacts on the relevance performance indicators. External environment was evaluated from dimensions of uncertainty, domain consensus, heterogeneity, capacity and dynamism. The findings of this study indicate statistically significant positive relationship between external environment and CBOs external environment and effectiveness (beta 0.541, p-value=0.000), efficiency (beta 0.695, p-value=0.000), relevance (beta 0.707, pvalue= 0.000) and financial viability (beta 0.578, p-value=0.000) leading to an argument that proper scanning of external environment influences all activities of an organization from planning to implementation. However, extra attention should be paid to external environment in program identification and planning as this shapes implementation. This study has important implications for managers of CBOs on the relevance of proper scanning of external environment as it influences all activities of an organization from program conceptualization to implementation.